TINDAK TUTUR EKSPRESIF DALAM FILM JELITA SEJUBA: MENCINTAI KESATRIA NEGARA - Sri Dwi Yulianti; Muhammad Saleh (Universitas Negeri Makassar, 2022)
Expressive speech acts in the film Jelita Sejuba: Loving the Knights of the Country. This study aims to: (1) describe the form of expressive speech acts in the film Jelita Sejuba: Loving the Kesatria Negara, (2) describe the expressive speech acts in the film